E-commerce adoption issues in Malaysian SMES - Hashim, Noor Azuan (2006)
E-commerce is said to convey undisputed benefits to companies everywhere, reshaping customer and supplier relationships, streamlining business processes and even restructuring whole industries. Managers are told that e-commerce will give a tremendous boost to their companies, that businesses not involved in e-commerce will be left behind in the global marketplace.Yet, e-commerce is not being adopted readily by SMEs. In fact, some studies claim that trading online by SMEs in some countries is stalling.Not many SMEs are keen to go online and only a few have websites.Drawing on existing research on ICT diffusion by SMEs, this paper explores e-commerce adoption by SMEs in Malaysia.It highlights preliminary findings from explorative telephone interviews with the SME managers.The main findings are that SMEs embrace e-commerce mainly because of pressure from customers.They also seek to improve company image, communications, information flow and contact with government.But many have no better reason for adopting e-commerce than that it is ‘nice to have’.Barriers to adoption include lack of technical knowledge and the failure rate of peers. Many think of e-commerce as ‘fancy stuff’, irrelevant to their sort of business.Implications are discussed.